Programming with Java IDL. - Lewis, Geoffrey, 1956- (John Wiley & Sons, Inc., 1998)
"This book is a guide to programming CORBA distributed objects in Java with Java IDL. This book is for developers who need to understand and work with systems that use both Java and CORBA, It's not only for people who work directly with the Sun Java IDL package, but also for people working with any CORBA Object Request Broker that conforms to the new OMG IDL-to-Java mapping specification. In this book, you will learn how to build systems using the technology that will become part of the foundation of future systems. CORBA object implementers will find this book useful for creating new shared services implemented in Java. Project managers and systems architects will find that this book is helpful in communicating the use of Java IDL without having to absorb all the minutiae in the specification itself, We hope that you will find the material in the book useful for both learning this technology and as a reference when you go on to build such systems of your own." (Copied from who should read this book?).